Novel long‐acting ropeginterferon alfa‐2b: Pharmacokinetics, pharmacodynamics and safety in a phase I clinical trial. Issue 5 (28th December 2021) - Huang, Yi‐Wen; Qin, Albert; Fang, Jane; Wang, Ting‐Fang; Tsai, Chung‐Wei; Lin, Ko‐Chung; Teng, Ching‐Leou; Larouche, Richard
Abstract : Aims: Ropeginterferon alfa‐2b is a novel, long‐acting pegylated interferon alfa‐2b. We aimed to evaluate its safety, pharmacokinetics (PK) and pharmacodynamics (PD). Methods: Thirty‐six subjects received single subcutaneous injection of ropeginterferon alfa‐2b at doses ranging from 24 to 270 μg, and 12 subjects received pegylated IFN alfa‐2a subcutaneously at 180 μg. Primary endpoints were safety/PK profiles of ropeginterferon alfa‐2b, while secondary endpoints were to compare PK/PD parameters with pegylated IFN alfa‐2a. Results: Adverse events in ropeginterferon alfa‐2b and pegylated IFN alfa‐2a groups were similar, and most of them were mild or moderate. Mean C max increased from 1.78 to 24.84 ng/mL along with the dose escalations in ropeginterferon alfa‐2b groups and was 12.95 ng/mL for pegylated IFN alfa‐2a. At 180 μg, ropeginterferon alfa‐2b showed statistically significant C max geometric mean ratio (1.76; P  = .0275). Mean T max ranged from 74.52 to 115.69 h for ropeginterferon alfa‐2b groups, and was 84.25 h for pegylated IFN alfa‐2a. Mean AUC0‐ t increased from 372.3 to 6258 ngh/mL with the dose escalations in the ropeginterferon alfa‐2b groups, while for pegylated IFN alfa‐2a it was found to be 2706 ngh/mL in pegylated IFN alfa‐2a. For neopterin and 2′, 5′‐oligoadenylate synthase, mean E max, T max and AUC0‐ t of ropeginterferon alfa‐2b were similar to those of pegylated IFNα‐2a at 180 μg. Conclusion: Ropeginterferon alfa‐2b up to 270 μg was safe and well tolerated. The PK/PD parameters of ropeginterferon alfa‐2b showed increase in dose–response. Ropeginterferon alfa‐2b had higher drug exposures and showed similar safety profile when compared to pegylated IFN alfa‐2a at the same dose level.